Economic growth in Malaysia : projections of gross national product and of production, consumption, and net imports of agricultural commodities - Crosson, Pierre R.; Center for Development Planning, National Planning Association (Jerusalem : Pubilshed for the U.S. Department of Agriculture, Economic Research Service [by] the Israel Program for Scientific Translations, 1966)
The book have two principal objectives: 1 to analyze and project to 1965, 1970 and 1975 both Gross National Product (GNP) and private consumption in Malaysia. 2, consistent with these aggregative projections, to project for each of these areas local production, demand, and net imports of the following commodities: rice, wheat and wheat flour etc.
Includes bibliographical footnotes.
hza 31/01/2019
Loans
Keywords: Economic history; Malaysia